HUKUM ISLAM DAN FENOMENA DROPSHIPPING: STUDI KRITIS TRANSAKSI JUAL BELI ONLINE - Habibah Zulaiha; Sofia Rismawati; Rusman Suheri (Yayasan Baitul Hikmah al-Zain, 2025)
The phenomenon of dropshipping as an online business model is becoming increasingly popular in the digital economy era due to its ease for sellers to market products without the need to keep stock. However, this system raises legal questions, particularly regarding its validity under Islamic law. This study aims to examine dropshipping practices through an Islamic legal approach, conducting a critical analysis of the contract, ownership of goods, and fulfillment of the conditions and requirements of a sale. The research method used is qualitative with a normative approach, referencing primary sources of Islamic law such as the Quran, Hadith, and fiqh muamalah literature, as well as secondary sources in the form of electronic commerce regulations in Indonesia. The findings indicate that dropshipping can be justified under Sharia law if it meets certain conditions, such as clarity of the transaction object (ma’qud ‘alaih), transparency of information, and the absence of elements of gharar or fraud. The contract used must be adapted, for example, through a wakalah or salam contract, to ensure compliance with Sharia principles. This study recommends the need for contemporary fiqh guidelines regulating dropshipping practices so that businesses can operate in accordance with positive law and in harmony with Islamic values.